Terrorism and Developing Countries - Abdul Rehman Khan, Syed; Yu, Zhang; Abdul Rehman Khan, Syed; Yu, Zhang (IntechOpen, 2020)
Bioterrorism is terrorism involving the intentional dissemination of biological agents. As in biological warfare, bioterrorism agents can be viruses, fungi, bacteria, toxins, insects or any other number of naturally occurring or synthetic agents. Therefore, it can be difficult for clinicians to discriminate between an act of terrorism and a naturally occurring outbreak.Written by distinguished researchers in the field, this book examines the effects of bioterrorism and terrorism on the socioeconomic sustainability of different countries around the globe.
English
Keywords: Sociology; Sociology